1998
DOI: 10.1029/1998gl900089
|View full text |Cite
|
Sign up to set email alerts
|

First observation of meteoritic charged dust in the tropical mesosphere

Abstract: Abstract.We discuss a recent sounding rocket experiment which found charged dust in the Earth's tropical mesosphere. The dust detector was designed to measure small (5000-10000 amu) charged dust particles, most likely of meteoric origin. A 5 km thick layer of positively charged dust was found at an altitude of 90 kin, in the vicinity of an observed sporadic sodium layer and sporadic E layer. The observed dust was positively charged in the bulk of the dust layer, but was negatively charged near the bottom.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
126
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(126 citation statements)
references
References 10 publications
0
126
0
Order By: Relevance
“…Havnes et al (1996) flew a Faraday cup through NLC and found negative particles but also positive particles in number densities too large to be accounted for by the standard plasma charging model. Positive particles have also been observed by detectors of different designs Smiley et al, 2003) and in the absence of NLC conditions (Gelinas et al, 1998;Rapp et al, 2005;Amyx et al, 2008). The possibility of photoelectric charging has been considered (Havnes et al, 1990;Rapp and Lübken, 1999), but this would require a reduction of the work function of ice by easily-ionized impurities such as sodium.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Havnes et al (1996) flew a Faraday cup through NLC and found negative particles but also positive particles in number densities too large to be accounted for by the standard plasma charging model. Positive particles have also been observed by detectors of different designs Smiley et al, 2003) and in the absence of NLC conditions (Gelinas et al, 1998;Rapp et al, 2005;Amyx et al, 2008). The possibility of photoelectric charging has been considered (Havnes et al, 1990;Rapp and Lübken, 1999), but this would require a reduction of the work function of ice by easily-ionized impurities such as sodium.…”
Section: Introductionmentioning
confidence: 91%
“…The aerosol particles reside in the D-region of the ionosphere and thus create dusty plasma (Goertz, 1989) of electrons, ions, and charged aerosol particles. Attachment of electrons to these aerosol particles reduces the electron mobility and allows the persistence of modulations in the electron Published by Copernicus Publications on behalf of the European Geosciences Union.…”
Section: Introductionmentioning
confidence: 99%
“…This lack of knowledge is mainly due to the complications involved in measurements at these altitudes where in situ studies only can be carried out using sounding rockets. Because of the difficulties in detecting neutral particles, measurements of nanometre-sized particles in the mesosphere are so far only 4416 L. Megner et al: Meteoric smoke particle distribution available for the charged fraction of the total particle population (Schulte and Arnold, 1992;Gelinas et al, 1998;Croskey et al, 2001;Lynch et al, 2005;Rapp et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Among these are the nucleation of mesospheric ice particles (e.g., Rapp and Thomas, 2006), the mesospheric metal chemistry , the D-region charge balance (e.g., Rapp and Lübken, 2001), the heterogeneous formation of water vapour in the mesosphere (Summers et al, 2001), and even the nucleation of polar stratospheric cloud particles which play a major role in the formation of the ozone hole (e.g., Voigt et al, 2005). While some progress regarding the experimental investigation of these atmospheric trace species has been made over the past years with sounding rockets (e.g., Schulte and Arnold, 1992;Gelinas et al, 1998;Horányi et al, 2000;Rapp et al, 2005;Lynch et al, 2005;Barjatya and Swenson, 2006;Amyx et al, 2008;Strelnikova et al, 2009;Rapp et al, 2010), incoherent scatter radars Strelnikova et al, 2007;Fentzke et al, 2009), satellites (Hervig et al, 2009(Hervig et al, , 2012, and laboratory studies (Saunders and Plane, 2006), much of our knowledge about these particles still relies on model results (e.g., Hunten et al, 1980;Gabrielli et al, 2004;Megner et al, 2006Megner et al, , 2008Bardeen et al, 2008). Among other things, very little is still known about the physical and chemical properties of MSPs such as their composition and their electrical and optical properties.…”
Section: Introductionmentioning
confidence: 99%